Pernikahan Arab Pra-Islam: Dialektika Tradisi Jahiliyah dengan Hadis Nabi - Dian Syah Fikri Alfani, Nur; bin Asis, Joharis; Syaikhu, Muhamad; Hamsa Fauriz, Mohammad (El Nubuwwah Jurnal Studi Hadis, 2025)
Pre-Islamic Arab marriage practices were embedded in a patriarchal socio-cultural structure that frequently disadvantaged women, particularly through unrestricted polygamy and asymmetrical marital authority. This cultural configuration constituted the socio-historical context to which the Sunnah of the Prophet responded through normative guidance rather than radical rupture. This article examines the dialectical interaction between pre-Islamic Arab marriage traditions and the normative formation of Islamic marital law through the lens of hadith studies, employing Hegelian dialectics as an analytical framework. The study adopts a qualitative descriptive-analytical approach based on library research, utilizing prophetic traditions related to marriage and polygamy as primary sources, complemented by classical hadith commentaries, Qur’anic exegesis, Islamic legal theory, and socio-historical scholarship as secondary sources. Data analysis is conducted through thematic hadith analysis, contextual interpretation, and dialectical mapping, in which pre-Islamic marriage customs are positioned as the thesis, the normative response of the Sunnah as the antithesis, and the resulting Islamic legal norms as the synthesis. The findings indicate that the Sunnah functioned as a mediating normative force that selectively preserved, modified, and reoriented existing marital practices toward ethical rationality and justice, rather than negating them entirely. In particular, the regulation of polygamy reflects a dialectical synthesis that transformed a culturally embedded practice into a morally accountable legal institution. This study contributes to hadith scholarship by demonstrating that the Prophet’s normative responses represent a dynamic process of socio-legal transformation, wherein Islamic law emerges through contextual engagement with, rather than detachment from, pre-Islamic cultural realities.